Psychosocial Determinants of Antenatal Care Utilisation in Palopo City, Indonesia: An Integrated Health Belief Model and Intention-Based Approach - Dyah Tahir; Evawati Uly; Fadli Fadli; Andi Sastria Ahmad (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Antenatal care (ANC) is an essential maternal health service for preventing pregnancy complications. However, ANC utilisation remains suboptimal in many developing countries, including Indonesia. This study examined psychosocial determinants associated with ANC utilisation using an integrated Health Belief Model and an intention-based behavioural framework among pregnant women in Palopo City, Indonesia. Methods: A cross-sectional study was conducted among 109 pregnant women in the second and third trimesters at Pontap Health Center, Palopo City, Indonesia. Data were collected using a structured questionnaire and analysed using partial least squares structural equation modelling (PLS-SEM) to examine direct and indirect associations among psychosocial constructs, intention, and ANC behaviour. Results: Knowledge was inversely associated with intention (β = -0.410; p = 0.030), while risk perception (β = 0.333; p < 0.001), subjective norms (β = 0.187; p = 0.001), and self-efficacy (β = 0.893; p < 0.001) were positively associated with intention. Intention was positively associated with ANC behaviour (β = 0.598; p < 0.001). In contrast, knowledge and self-efficacy did not have significant direct associations with ANC behaviour. The reported indirect effects suggest a potential mediating role for intention. These findings highlight psychosocial and intention-based pathways associated with ANC behaviour among pregnant women in Indonesia. Conclusion: This study highlights the association between psychosocial factors, particularly behavioural intention, and ANC behaviour among pregnant women. Health-promotion strategies that address risk perception, subjective norms, and self-efficacy may support ANC attendance. Longitudinal and intervention studies are needed to examine these relationships over time.